Religious Movements to the Rescue in Transit? Exploring the Role of the Church of Pentecost in the Lives of Ghanaian Immigrants in Istanbul - Dotsey, Senyo (PARTECIPAZIONE E CONFLITTO, 2020)
This exploratory article uses qualitative data to critically document how social networks developed around the Church of Pentecost (CoP) Istanbul, and how the ensuing social capital accumulation has somewhat played significant roles in the lives of Ghanaian immigrants in a transit environment, Istanbul (Turkey). The paper argues that with immigrants caught within webs of unreceptive and strict legal environments, socio-economic, moral, psychological, identity, and spiritual struggles in the host country, these Churches, such as the CoP Istanbul, have somewhat become crucial resource pools that immigrants, be they irregular, regular or so-called 'transit migrants' and asylum-seekers, draw on to provide solutions to these quotidian existential problems. The findings documented herein enrich the African Diaspora and religious movements' literature, illuminating how these movements shape immigrants' lives in transit destinations like Turkey.